Genome-wide analysis of RNA-binding proteins co-expression with alternative splicing events in mitral valve prolapse - Zhao, Meng; Zhou, Jingxin; Tang, Yihu; Liu, Mingzhu; Dai, Yawei; Xie, Hui; Wang, Zihao; Chen, Liang; Wu, Yanhu (Frontiers in Immunology, 2023)
Objectives We investigated the role and molecular mechanisms of RNA-binding proteins (RBPs) and their regulated alternative splicing events (RASEs) in the pathogenesis of mitral valve prolapse (MVP). Methods For RNA extraction, we obtained peripheral blood mononuclear cells (PBMCs) from five patients with MVP, with or without chordae tendineae rupture, and five healthy individuals. High-throughput sequencing was used for RNA sequencing (RNA-seq). Differentially expressed genes (DEGs) analysis, alternative splicing (AS) analysis, functional enrichment analysis, co-expression of RBPs, and alternative splicing events (ASEs) analysis were conducted. Results The MVP patients exhibited 306 up-regulated genes and 198 down-regulated genes. All down- and up-regulated genes were enriched in both Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Furthermore, MVP was closely associated with the top 10 enriched terms and pathways. In MVP patients, 2,288 RASEs were found to be significantly different, and four suitable RASEs (CARD11 A3ss, RBM5 ES, NCF1 A5SS, and DAXX A3ss) were tested. We identified 13 RNA-binding proteins (RBPs) from the DEGs and screened out four RBPs (ZFP36, HSPA1A, TRIM21, and P2RX7). We selected four RASEs based on the co-expression analyses of RBPs and RASEs, including exon skipping (ES) of DEDD2, alternative 3′ splice site (A3SS) of ETV6, mutually exclusive 3′UTRs (3pMXE) of TNFAIP8L2, and A3SS of HLA-B. Furthermore, the selected four RBPs and four RASEs were validated by reverse transcription–quantitative polymerase chain reaction (RT-qPCR) and showed high consistency with RNA sequencing (RNA-seq). Conclusion Dysregulated RBPs and their associated RASEs may play regulatory roles in MVP development and may therefore be used as therapeutic targets in the future.